1999
DOI: 10.1159/000008054
|View full text |Cite
|
Sign up to set email alerts
|

The 14-3-3 Protein Detectable in the Cerebrospinal Fluid of Patients with Prion-Unrelated Neurological Diseases Is Expressed Constitutively in Neurons and Glial Cells in Culture

Abstract: The 14-3-3 protein belongs to a family of 30-kD proteins originally identified by two-dimensional analysis of brain protein extracts. Recently, the detection of the 14-3-3 protein in the cerebrospinal fluid (CSF) is utilized as a highly reliable test for the premortem diagnosis of prion diseases such as Creutzfeldt-Jakob disease. For the initial step, to clarify the biological implication of the CSF 14-3-3 protein in these diseases, its expression was investigated in neural tissues and cultures and CSF samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 32 publications
1
59
1
5
Order By: Relevance
“…Stratifin (SFN, or 14-3-3) is a member of a large family of highly conserved 14-3-3 proteins, which are known to function as intracellular chaperones in signal transduction, apoptosis and cell cycle regulation (Hermeking, 2003;Pozuelo et al, 2004). Several groups have reported on the presence of 14-3-3 proteins in the extracellular space (Butler and Overall, 2009a;Katz and Taichman, 1999;Kobayashi et al, 2009;Leffers et al, 1993;Satoh et al, 1999). Our group has recently identified a novel function for the keratinocyte-releasable form of SFN as a potent MMP-1-stimulatory factor in dermal fibroblasts (Ghahary et al, 2004).…”
Section: Introductionmentioning
confidence: 81%
“…Stratifin (SFN, or 14-3-3) is a member of a large family of highly conserved 14-3-3 proteins, which are known to function as intracellular chaperones in signal transduction, apoptosis and cell cycle regulation (Hermeking, 2003;Pozuelo et al, 2004). Several groups have reported on the presence of 14-3-3 proteins in the extracellular space (Butler and Overall, 2009a;Katz and Taichman, 1999;Kobayashi et al, 2009;Leffers et al, 1993;Satoh et al, 1999). Our group has recently identified a novel function for the keratinocyte-releasable form of SFN as a potent MMP-1-stimulatory factor in dermal fibroblasts (Ghahary et al, 2004).…”
Section: Introductionmentioning
confidence: 81%
“…Several neurological diseases including CJD are characterized by increased brain expression, deposition or CSF release of protein 14-3-3. Reports on CSF 14-3-3 in GBS are controversial, presumably due to methodological differences between the studies [2,62]. While CSF 14-3-3 could function as another unspecific marker of neuronal damage, clinical relevance in GBS seems to be small at the present state.…”
Section: Protein 14-3-3mentioning
confidence: 99%
“…Although more than 100 proteins have been reported to interact with intracellular members of 14-3-3 family [Pozuelo et al, 2004], functional activities of the releasable forms of these proteins in general and 14-3-3 s, in particular, are completely unknown. In fact, the presence of 14-3-3 proteins in cerebral spinal fluid [Satoh et al, 1999] as well as KCM [Katz and Taichman, 1999] has been previously reported, without designating any function. Our group has recently identified and characterized a keratinocyte-releasable anti-fibrogenic factor (KDAF) for dermal fibroblasts, which was discovered to be a releasable form of stratifin.…”
mentioning
confidence: 99%